PENAMBANGAN BATU SPLIT YANG MENYISAKAN KELERENGAN TERJAL DI DAERAH AWANGBANGKAL, KECAMATAN KARANGINTAN, KABUPATEN BANJAR, PROVINSI KALIMANTAN SELATAN - Jarwanto Jarwanto (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2021)
Mining of split rock or ultramafic igneous rock, located in the Awangbangkal area, Karangintan District, Banjar Regency, South Kalimantan Province, causes steep slopes. The formation of the Meratus Mountains is an oceanic bedrock that is exposed to the earth's surface and is mined by local residents using simple tools or semi-mechanical equipment carried out by the company. Positive impacts arise but negative impacts will also build up over time. Day by day more dangerous slopes were formed. The local government became worried because it was dangerous. This writing is compiled based on the results of direct measurements in the field using the Theodolith unit. The measurement results are processed using Autocad Landesktop 2009 software. The analysis is by classifying the slope of the formed slopes according to the data that is already in digitized form. The result is a dangerous area on the east side, because it has a slope of 25% -45% (steep). Although from a geological point of view this area is stable because it is formed by igneous rocks, from the local government side this is a concern for the people who do work in the area.